Pregunta
If \( f(x)=-3 x-4, g(x)=3 x^{2}+6 x+3 \), and \( h(x)=-5 x^{2}-6 \), find \( g(1) \)
Ask by Bob Hanson. in the United States
Feb 02,2025
Solución de tutoría real
Respuesta verificada por el tutor
Responder
\( g(1) = 12 \)
Solución
To find \( g(1) \) for the function \( g(x) = 3x^{2} + 6x + 3 \), follow these steps:
1. **Substitute \( x = 1 \) into the function:**
\[
g(1) = 3(1)^{2} + 6(1) + 3
\]
2. **Calculate each term:**
- \( 3(1)^{2} = 3 \times 1 = 3 \)
- \( 6(1) = 6 \)
- The constant term is \( 3 \)
3. **Add the results:**
\[
g(1) = 3 + 6 + 3 = 12
\]
**Therefore, \( g(1) = 12 \).**
Revisado y aprobado por el equipo de tutoría de UpStudy
Como
error msg
Explicar
Simplifique esta solución
Bonus Knowledge
To find \( g(1) \), we need to substitute \( x = 1 \) into the function \( g(x) = 3x^{2} + 6x + 3 \). Calculating it step-by-step: 1. Substitute \( x = 1 \): \[ g(1) = 3(1)^{2} + 6(1) + 3 \] 2. Evaluate \( (1)^{2} \): \[ g(1) = 3(1) + 6 + 3 \] 3. Calculate \( 3(1) + 6 + 3 \): \[ g(1) = 3 + 6 + 3 = 12 \] Thus, \( g(1) = 12 \).
¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde
Hazte Premium